Farm irrigation : planning & management - Southorn, Neil (Practical farming., 1997)
There is no doubt that irrigation makes a major contribution to agricultural production, making a whole range of crops viable in an otherwise unreliable climate and helping insure against drought. However irrigation does not automatically guarantee a profit and acclaim, it is a high cost exercise, using water from increasingly scarce supplies, and contributes to environmental concerns of the community. Many of the pressures facing some irrigators have been caused by a lack of understanding in the past of best practices necessary in design, installation and management. Alternative methods of ir.